Effect of a high dose atorvastatin as added-on therapy on symptoms and serum AMPK/NLRP3 inflammasome and IL-6/STAT3 axes in patients with major depressive disorder: randomized controlled clinical study - Aldossary, Khlood Mohammad; Ali, Lashin Saad; Abdallah, Mahmoud S.; Bahaa, Mostafa M.; Elmasry, Thanaa A.; Elberri, Eman I.; Kotkata, Fedaa A.; El Sabaa, Ramy M.; Elmorsi, Yasmine M.; Kamel, Mostafa M.; Negm, Walaa A.; Elberri, Aya Ibrahim; et al. (Frontiers in Pharmacology, 2024)
Background Neuroinflammation pathways have been associated with the development of major depressive disorders (MDD). The anti-inflammatory characteristics of statins have been demonstrated to have significance in the pathophysiology of depression. Aim To investigate the mechanistic pathways of high dose atorvastatin in MDD. Patients and methods This trial included 60 patients with MDD who met the eligibility requirements. Two groups of patients (n = 30) were recruited by selecting patients from the Psychiatry Department. Group 1 received 20 mg of fluoxetine plus a placebo once daily. Group 2 received fluoxetine and atorvastatin (80 mg) once daily. All patients were assessed by a psychiatrist using the Hamilton Depression Rating Scale (HDRS). A HDRS score of ≤7 indicates remission or partial remission [HDRS<17 and>7]. Response was defined as ≥ 50% drop in the HDRS score. The serum concentrations of nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-3 (NLRP-3), interleukin-6 (IL-6), adenosine monophosphate activated protein kinase (AMPK), and signal transducer and activator of transcription factor-3 (STAT-3) were measured. Results The atorvastatin group showed a significant reduction in the levels of all measured markers along with a statistical increase in the levels of AMPK when compared to the fluoxetine group. The atorvastatin group displayed a significant decrease in HDRS when compared to its baseline and the fluoxetine group. The response rate and partial remission were higher in the atorvastatin group than fluoxetine (p = 0.03, and p = 0.005), respectively. Conclusion These results imply that atorvastatin at high doses may be a promising adjuvant therapy for MDD patients by altering the signaling pathways for AMPK/NLRP3 and IL-6/STAT-3. Clinical Trial Registration clinicaltrials.gov, identifier NCT05792540.